PELATIHAN KETERAMPILAN BERBICARA DALAM BAHASA INGGRIS DENGAN MENGGUNAKAN METODE PRESENTATION, PRACTICE, AND PRODUCTION (PPP) BAGI SISWA SD DI KELURAHAN TUNGGURONO KOTA BINJAI - Anna Stasya Prima Sari; Ribka Kariani Br Sembiring (Universitas Serambi Mekkah, 2019)
This community service is primarily aimed to give English speaking skill training to primary school students at Tunggurono village, Binjai by applying Presentation, Practice, and Production (PPP) method. This community service was conducted for two days, namely on Saturday, 05th October 2019 - Sunday, 06th October 2019 at 03.30 p.m.-05.00 p.m. The participants of this community service are the primary school students (six-twelve years old children) at Tunggurono village, Binjai. There are 14 students as the participants. PPP method is one of alternatives which can be applied to create an effective and interesting atmosphere of learning teaching English speaking skill. The application of this method functions to connect new information got by the students with their knowledge. Therefore, this method gives chance to the students to apply and develop their ideas or opinions critically and communicatively. It is expected that the primary school students at Tunggurono village, Binjai are more motivated and confident in speaking English and have chance to enhance their English speaking skill.